Carrier RNA is a key factor affecting fully integrated short tandem repeats profiling in challenging forensic samples models - Haidan M. El-Shorbagy; Shereen S. El-Liethy; Mona K. Moussa; Akmal A. Elghor (Journal of Basic and Applied Zoology, 2022)
Abstract Background Short tandem repeats (STRs) are used today to provide discriminatory power for DNA fingerprinting. The present results showed that different factors may affect STR profiles in challenging samples including DNA quantity, DNA quality, PCR inhibitors and storage time. In the present study, blood stain samples were applied on two types of fabrics (black cotton and denim) to compare the efficiency of two different DNA-extraction methods (automated magnetic based beads method (EZ1), and manual organic method), with and without adding carrier RNA molecules, and to assess the quality and quantity of the extracted DNA and their capabilities for producing reportable STR-profiles in the presence of PCR inhibitors at two different storage times. Results Carrier RNA caused a dramatic increase in DNA recovery from black cotton or denim using EZ1 in contrast to organic method. EZ1 was found to be preferred than organic, especially when a time passed over, while organic method was preferred when samples are available in small quantities. In addition, using carrier RNA within the organic method steps showed no improvement in STR profiling. EZ1 with carrier RNA was preferred for bloodstained samples on fabrics with textile dyes (black dye or denim indigo), especially when stored for a long time. Conclusions Denim was found to be more problematic than black cotton due to presence of challenging inhibitors (indigo dye). DNA concentration, storage time and types of fabrics are key factors for choosing the appropriate extraction method for reportable STR profile. Using EZ1 with carrier RNA gives less dropout profile than not using it, or when using organic method even in presence or absence of carrier RNA. Anyway, innovation of more sensitive, more robust analytical protocols could result in a better understanding of these inhibitory samples.